The Effect Of E-Service Quality on Purchase Decisions with Consumer Trust as a Mediating Variable - Aini, Safira Nur; Juliati, Ratih; Putri, Viajeng Purnama (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research was conducted on Grosir Asemka consumers who made purchases through the Shopee marketplace, with the aim of the study to determine: the effect of e-service quality on purchasing decisions, es-service quality on consumer trust, consumer trust in purchasing decisions and e-service quality on purchasing decisions through consumer trust. This research uses the SPSS 25 for Windows Program tool, and uses 125 respondents. The results of this study are as follows: e-service quality has a positive and significant effect on purchasing decisions, e-service quality has a positive and significant effect on consumer trust, consumer trust has a positive and significant effect on purchasing decisions, and consumer trust has a mediating role in the relationship between e-service quality and purchasing decisions.